SYNTHESIS OF AMINO DERIVATIVES OF MONOTHIO- AND DITHIO- ANALOGUES OF CYCLOHEXANESPIRO-5-HYDANTOIN - Marinov, Marin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
This article presents methods for synthesis of 3-amino derivatives of cyclohexanespiro-5-(2-thiohydantoin) and cyclohexanespiro-5-(2,4-dithiohydantoin). It was found out that the treatment of cyclohexanespiro-5-(2-thiohydantoin) with hydrazine hydrate under different reaction conditions led to obtaining of 3-amino derivative and 2-hydrazone of the initial compound. As a result of thionation of 3-aminocyclohexanespiro-5-hydantoin with P4S10 or Lawesson’s reagent, the corresponding dithio-analogue was synthesized. The structures of the products obtained were verified by IR, 1H NMR, 13C NMR and mass spectral data.